Replace y with -3x in the second equation.
-3x - x = 5
-4x = 5
x = -5/4
Now replace x with -5/4 in the first equation.
y = -3(-5/4) = 15/4
Answer: (-5/4, 15/4)
2007-01-11 10:21:53
·
answer #1
·
answered by MsMath 7
·
2⤊
0⤋
You'll want to use what's called substitution. The first equation tells you:
y = -3x
The second
y - x = 5
Now we want to solve for x and y. Well the first equation tells us that y is -3x. So we know what y is. y is -3x. In the second equation if we plug in -3x for y we'll get this.
-3x - x = 5
That probably looks a little nicer for you. You only have one variable. Go ahead and combine like terms.
-3x plus -x = -4x so...
-4x = 5
To get x by itself let's divide both sides by -4.
x = -5/4 Now that we know what x equals, we can plug in this value for x in either equation. I think the second equation would be easier but I'll do both.
y = -3x
or with our new value for x...
y = -3(-5/4)
Multiplying through we get
y = 15/4 or 3 3/4
Using the second equation.
y - x = 5
or with our new value for x...
y - (-5/4) = 5
We know a double negative is a positive so we can rewrite like this...
y + 5/4 = 5
Solving for y we'd subtract 5/4 from both sides and get
y = 5 - 5/4 or
y = 4 4/4 - 1 1/4
y = 3 3/4
Notice we get the same answer for y regardless of which equation we use.
The trick here is to solve either equation for one variable. Once we know what the one variable is, we can plug that value (or equation) for the variable in the other equation. Since the first equation was solved for y (meaning y = something) we plugged that value in for y in the second equation. I hope this helps.
Your answers are:
x = -5/4
y = 3 3/4
Good luck in your math.
2007-01-11 10:31:39
·
answer #2
·
answered by Chaney34 5
·
0⤊
0⤋
To solve your question, you need to make substitutions
y = -3x & y - x = 5
Try substituing for y in y - x = -5
.....y - x = -5
(-3x) - x = 5
.......-4x = 5
..........x = -5/4 (you now know the value of x)
......y - x = 5 (now find the value of y)
y - (-5/4) = 5 (substitute the value of x)
...........y = 5 - ( 5/4) = 20/4 - 5/4 = 15/4
OR
y = -3x
y = -3(-5/4) = 15/4
2007-01-11 10:33:22
·
answer #3
·
answered by srrl_ferroequinologist 3
·
0⤊
0⤋
Get the x's and y's on the same side of each equation.
y + 3x = 0
y - x = 5
Then add or subtract the two equations to get rid of one of the variables. Since there's just one y in each equation, you can do the first equation minus the second equation.
y + 3x - (y - x) = 0 - 5
Then simplify each side.
y + 3x - y + x = -5
4x = -5
x = -5/4 = - 1 1/4
Substitute the value for x in one of the original equations.
y = -3x
y = (-3/1)(- 5/4)
y = 15/4 = 3 3/4
Check to see if it works by substituting for x and y in the second equation.
y - x = 5
15/4 - (-5/4) = 5
15/4 + 5/4 = 5
20/4 = 5
It's correct!
2007-01-11 10:27:47
·
answer #4
·
answered by ecolink 7
·
0⤊
0⤋
-3x - x = 5
-4x = 5
x = - 5/4
then with the answer, just solve for y
2007-01-11 10:24:33
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
Subtract the two equations,
x = -3x-5
Solve for x,
x = -5/4
y = 15/4
2007-01-11 10:22:38
·
answer #6
·
answered by sahsjing 7
·
0⤊
0⤋
If you know that y= -3x, then substitute this into your other equation for the value of y.
-3x - x = 5
-4x = 5 (you will need to multiply both sides to get rid of the negative. you never want a negative variable)
4x = -5
x = -5/4
x = -1.25
Then you take your value for x and substitute it into either equation. Make sure you check it by putting x and y into both equations and they should be true.
2007-01-11 10:26:26
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
-x + y = 2 x=y-2 change into the different 2 equations x – 2z = -5 y - 2 -2z = -5 y-2z = -3 3x – y + 2z = 6 3(y-2) - y + 2z = 6 3y-6-y+2z = 6 2y+2z-6 = 6 y+z = 6 Now subtract the first equation from the second one y+z - (y-2z) = 6 - -3 3z = 9 z = 3 y+z = 6, so y = 3 x= y-2, x = a million (a million,3,3)
2016-11-23 12:44:47
·
answer #8
·
answered by ? 4
·
0⤊
0⤋
Substitution
-3x-x=5
-4x=5
x=-5/4 or -1.20
y=-3(-5/4)
y=-2.40
2007-01-11 10:23:55
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
y=-3x
y-x=5
-3x-x=5
-4x=5
x= -5/4
y= -3(-5/4)
y= 15/4
2007-01-11 10:23:42
·
answer #10
·
answered by 7
·
0⤊
0⤋